2019
DOI: 10.1007/s10509-019-3596-y
|View full text |Cite
|
Sign up to set email alerts
|

On the relaxed states in the mixture of degenerate and non-degenerate hot plasmas of astrophysical objects

Abstract: It is shown that a small contamination of a relativistically hot electron component can induce a new scale (for structure formation) to a system consisting of an ion-degenerate electron plasma. Mathematically expression of this additional scale length is the increase in the index of quasi-equilibrium Beltrami-Bernoulli states that have been invoked to model several astrophysical systems of interest. The two species of electrons, due to different origin of their relativistic effective masses, behave as two dist… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 54 publications
1
15
0
Order By: Relevance
“…2 for an example). These results, as embodied by the equations ( 25) and ( 26), are qualitatively similar, albeit derived from a more generic standpoint, to the generalized magneto-Bernoulli mechanism elucidated in Ohsaki et al (2001); Mahajan et al (2002); Shatashvili et al (2019); it has been proposed that this mechanism may constitute a viable explanation for solar flares (Kagan & Mahajan 2010), as opposed to classic paradigms such as fast magnetic reconnection (Biskamp 2000;Shibata & Magara 2011;Comisso et al 2016).…”
Section: Helicity Constraints On Turbulencesupporting
confidence: 65%
“…2 for an example). These results, as embodied by the equations ( 25) and ( 26), are qualitatively similar, albeit derived from a more generic standpoint, to the generalized magneto-Bernoulli mechanism elucidated in Ohsaki et al (2001); Mahajan et al (2002); Shatashvili et al (2019); it has been proposed that this mechanism may constitute a viable explanation for solar flares (Kagan & Mahajan 2010), as opposed to classic paradigms such as fast magnetic reconnection (Biskamp 2000;Shibata & Magara 2011;Comisso et al 2016).…”
Section: Helicity Constraints On Turbulencesupporting
confidence: 65%
“…The nonlinear wave dynamics will be studied for a quasi neutral unmagnetized plasma of an immobile classical ion component (i), and two electron species -the bulk relativistic degenerate (d) electron gas with a density N 0d and a small contamination of non-degenerate classical (cl) electrons with density N 0cl [15]. Quasi neutrality demands…”
Section: Modelmentioning
confidence: 99%
“…To study the nonlinear propagation of intense EM waves, the multicomponent plasma dynamics has to be coupled (see [15]) with the Maxwell equations,…”
Section: Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…These studies have shown the generation/amplification of fast macro-scale plasma flows in the degenerate two-fluid astrophysical systems, for which the simplest relaxed states are described by double Beltrami condition, which states that the generalized flow is aligned with its vorticity augmented by the Bernoulli condition. Shatashvili et al (2019) have shown that in a quasi neutral plasma of a bulk degenerate electrons contaminated by small fraction of a non-degenerate highly relativistic hot electron component can induce a new scale (for structure formation) to a system consisting of an ion-degenerate electron plasma. Determined by concrete parameters of the system, new macro-scale lengths (much larger than short intrinsic scale lengths [skin depths] and generally much shorter than system size) open new pathways for energy transformations.…”
Section: Introductionmentioning
confidence: 99%